2017
DOI: 10.2147/ccide.s149545
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic-avascular osteonecrosis: local “silent inflammation” in the jawbone and RANTES/CCL5 overexpression

Abstract: Of the definitions listed in the International Statistical Classification of Diseases and Related Health Problems, tenth revision (ICD-10), two disease descriptions can be found together: “idiopathic aseptic bone necrosis” and “avascular bone necrosis.” The relevant literature on both the conditions abbreviates both as “aseptic ischemic osteonecrosis in the jawbone” (AIOJ). To shed light on the clinical details of this condition, osteolytic jawbone samples of 24 patients with different systemic immunological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Bacterial events, which are usually associated with high levels of TNF-α and IL-6 expression, could be ruled out within the FDOJ area. 60 Thus, R/C overexpression alone is involved in the characteristic and bone-degrading element of an FDOJ. TNF-α and IL-6 signaling in all other bone resorptive processes are excluded ( Figure 10 ).…”
Section: Discussion: In Bone Resorption Except For Fdoj Tnf-a Is Thmentioning
confidence: 99%
“…Bacterial events, which are usually associated with high levels of TNF-α and IL-6 expression, could be ruled out within the FDOJ area. 60 Thus, R/C overexpression alone is involved in the characteristic and bone-degrading element of an FDOJ. TNF-α and IL-6 signaling in all other bone resorptive processes are excluded ( Figure 10 ).…”
Section: Discussion: In Bone Resorption Except For Fdoj Tnf-a Is Thmentioning
confidence: 99%
“…The authors examined in detail the tissue in such jaw lesions that appears as fatty lumps inside an intact cortical bone. 6,7 They showed that the fatty lumps found are biochemically extremely active and produce certain cytokines in large quantities, in particular the chemokine RANTES/CCL-5 (R/ C). The expression levels of these cytokines are also elevated in a number of systemic diseases such as cancer, dementia, multiple sclerosis or arthritis.…”
Section: Morphology Of Bmd/aioj/fdoj and Local Rantes/ Ccl5 Expressionmentioning
confidence: 99%
“…However, in most of these cases, the local effect of neuralgic pain is missing. 6,7,21,22 It has also been plausibly shown that AIOJ/BMD/FDOJ describes the pathological condition of the jawbone, which is listed in code M87.0 of the ICD-10 (International Code of Diseases, Tenth Revision (ICD-10)). Figure 7 on the right shows the typical fatty-degenerative morphology of a BMD/AIOJ/FDOJ sample.…”
Section: Morphology Of Bmd/aioj/fdoj and Local Rantes/ Ccl5 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal immune response, imbalanced immune cell subpopulations, and higher plasma levels of inflammatory cytokines in patients with osteonecrosis suggest that inflammation plays a crucial role in this disorder [ 12 14 ]. Moreover, chemokines and cytokines released by necrotic cells recruit inflammatory cells, inducing local and systemic immune response in patients with osteonecrosis [ 15 17 ]. However, whether these inflammatory processes are also involved in SCD osteonecrosis has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%